"It tastes like heaven": Critical and embodied food pedagogy with Black youth in the Anthropocene. Issue 7 (October 2019) - Jones, Naya
Young people who navigate intersecting racial, ethnic, economic, and/or geographic oppressions are often the objects of food pedagogy. Citing childhood obesity and anthropogenic environmental change, food pedagogies in the United States especially target Black/African-American youth, among other youth of color. Meanwhile, teaching and learning about food is on the rise in myriad settings, often in ways that reproduce binaries between "healthy" and "unhealthy" and "good" and "bad" foods. Grounded in hegemonic nutrition and bolstered by healthism, predominant food pedagogies perpetuate racialized assumptions about food and health. In the context of the Anthropocene as discourse and epoch, food pedagogy is likely to intensify, while climate change holds concerning implications for Black Americans. Critical and embodied approaches to food pedagogy are necessary, I argue, to address power relations and to cultivate community-led resilience. Building on Black geographies, critical food studies, and food pedagogies, I explore the possibilities of a critical and embodied pedagogy with Black American youth. I reflect on a "Favorite Meals" workshop carried out as part of an urban farm youth program in Austin, Texas, USA. Both the practice of the workshop and youth responses counter food binaries while highlighting pleasure, play, and knowledge—all of which remain underconsidered in food-related studies and pedagogy with young people. Given concerns about childhood obesity and the global scope of the Anthropocene, this article is relevant to food pedagogy with historically marginalized youth across national contexts.